Wrestling with the Unspeakable: The Exegete’s Subjective Experience as a Source for Theology - Feichtinger, Daniela (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
The reader’s subjective experience cannot be easily integrated into an interpretation that claims a certain objectivity and adequacy to the text. For the exegesis of sacred texts, this means that something unspeakable remains, the encounter of which is traditionally described with the theological categories revelation and salvation. This raises the suspicion that by methodically excluding subjectiveness, at least part of the theological character of a text gets lost in interpretation. In order to exemplify the challenge subjectivity poses to scientific interpretation, especially within the framework of a religious community, this paper analyzes documents of the Catholic Church on the interpretation of the bible since 1965. In a next step, the categories of revelation and salvation are traced in Roland Barthes’ essay Camera Lucida (1980). His concepts shed light on the shortcomings of the documents and provide fresh impulses for a transformed understanding and appreciation of the reader’s experience.